Adhesive bonding of discontinuous carbon fibre composites: an experimental investigation - Nicholls, Tristan Kit (2013)
The excellent specific stiffness and strength of carbon fibre reinforced polymer composites means that the automotive sector has been investigating methods of implementing these materials into structurally demanding applications. The work detailed within this thesis supports ongoing research at the University of Nottingham into the automated manufacture of discontinuous carbon fibre reinforced polymer composite materials. Advances in the automation of composites manufacturing has meant that methods to effectively join these materials is required. This work provides a fundamental understanding of the differences that result from the adhesive bonding of a discontinuous fibre composite (DFC) compared to conventional fibre reinforced composite materials.